(3GdebGeGJ GdRjfjIs - (3eYO Hf fUQ Gddg Hf QLH, CHh GdfOj TeS GdOjf GHf CHj GdaJM, GdeYQha HGHf GdUjbd GdLRQj,J (B701 (3g` s ((3eMeO Hf eMeO Hf eMehO GdSeQbfOj s)
(3ChdgG (B:s
(3hHYO, aEfj ONdJ PGJ jhe NjSj, hChjJ CfjSj s
(3BNQgG (B:s
(3hYhGFb bQjMJj dG JSJMb oHYhdG, hdcf djbVj Gddg CeQkG cGf eaYhdkG, JeJ GdebGeGJ GdRjfjI HYhf Gddg s
(3GfXQ GdLRA GdChd Qbe (B793 (3COHs
(3HgG WeS cKjQ ef CKQ JQbjY hShA JQejes
(3NeShf ebGeI Ydi fSb GdebGeGJ GdMQjQjIs
(3YRG QhGjJgG Edi GdbGSe Hf LQjGd GdOeTbjs
(3hVYgG dCHfg Rjf GdOjf haQZ ef JCdjagG SfI (B672(3g```s
(3fSNI NRGFfjI s
Keywords: (3GdCOHs